SASTRA ANAK SEBAGAI AWAL PENDIDIKAN KARAKTER DALAM CERPEN SERI “AKU MAU MENDENGARKAN”, “AKU BERANI BERTERIMAKASIH”, DAN “AKU MAU MEMAAFKAN” KARYA ADE YULIA - Nur Innayah Ganjarjati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
ABSTRACTThis research is about how literature, especially children’s literature canbe a character building for children. In literary works, the author has the purposeconveyed, moral, religious and political goals. To find out the objectives to beconveyed by the author, can be analyzed through pragmatics. In the series ofshort story entitled